Experimental Study on Family Formation and Moral Values of Students (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
The relevance of the research topic is due to the diversity and complexity of the tasks of human education in the 21st century. The modernization processes taking place in the modern Kazakhstani society created a deep crisis of many aspects of social life, including negatively affecting the value orientations of the younger generation, led to the devaluation of family values, alienation of youth from institutions of upbringing. This significant transformation partly led to a change in the orientations and priorities in the educational process of students.Analysis of the activity of higher education institutions in the education of family and moral values among students in the process of teaching and educational work made it possible to identify contradictions between:- the acute need of modern society for the upbringing of family and moral values among students and the underestimation of the significance of the process of family education in general;- the existing traditionally developed approach to determining the content of forms and methods of instruction and the objective needs of a qualitatively new attitude to the education of family and moral values among students in the process of education and educational work.This study allowed us to draw the following conclusions. The essence of the concept of "value" was substantiated, the content of the concept "family and moral values" was clarified on the basis of the analysis of scientific psychological and pedagogical literature. Experimental work was carried out among students of 1,2,3 courses of the specialty "Pedagogy and Psychology" of the Kazakh National Pedagogical University named after Abay, within the framework of which they tried to determine whether the family value is significant in the student environment.Justification of the novelty of the work. The authors attempted to reveal for the first time among students of a pedagogical university their real relation to the family, to family and moral values.